2017
DOI: 10.1177/0022146517736754
|View full text |Cite
|
Sign up to set email alerts
|

Couple-level Minority Stress: An Examination of Same-sex Couples’ Unique Experiences

Abstract: Social stress resulting from stigma, prejudice, and discrimination-"minority stress"-negatively impacts sexual minority individuals' health and relational well-being. The present study examined how being in a same-sex couple can result in exposure to unique minority stressors not accounted for at the individual level. Relationship timeline interviews were conducted with 120 same-sex couples equally distributed across two study sites (Atlanta and San Francisco), gender (male and female), and relationship durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 66 publications
1
88
0
3
Order By: Relevance
“…The movement toward the legalization of same‐sex marriage and increased acceptance of LGBTQ families has helped spur research assessing the lives of sexual minorities who wanted to become or were parents. For gay and lesbian adults wishing to raise children through adoption or using other means such as insemination, the process can be stressful because of discrimination and fraught within legal and medical systems that render certain decisions infeasible (Frost et al, ; Goldberg & Scheib, ; Karpman, Ruppel, & Torres, ; Vinjamuri, ). Many LGBTQ individuals have had children in prior heterosexual relationships or through becoming partners with someone who is already raising children (Gates, ).…”
Section: Parenting Minor Children In Social Contextmentioning
confidence: 99%
“…The movement toward the legalization of same‐sex marriage and increased acceptance of LGBTQ families has helped spur research assessing the lives of sexual minorities who wanted to become or were parents. For gay and lesbian adults wishing to raise children through adoption or using other means such as insemination, the process can be stressful because of discrimination and fraught within legal and medical systems that render certain decisions infeasible (Frost et al, ; Goldberg & Scheib, ; Karpman, Ruppel, & Torres, ; Vinjamuri, ). Many LGBTQ individuals have had children in prior heterosexual relationships or through becoming partners with someone who is already raising children (Gates, ).…”
Section: Parenting Minor Children In Social Contextmentioning
confidence: 99%
“…For example, qualitative and daily diary research suggests that gay and lesbian couples appear to be more concordant in health behavior (Holway, Umberson, & Donnelly, ; Reczek, ; Reczek & Umberson, ), are more likely to care for each other when sick (Thomeer, Reczek, & Umberson, ; Umberson, Thomeer, Reczek, & Donnelly, ), and are differentially impacted by marital strain (Garcia & Umberson, ) than heterosexual couples. Moreover, it appears that gay and lesbian couples face higher levels of discrimination and stress than heterosexual couples (Cao et al, ; Frost et al, ), and marriage bans are shown to worsen health among SGM people (Hatzenbuehler et al, , ; Kail, Acosta, & Wright, ). Gay and lesbian older adults who are legally married report better quality of life and more social and economic resources than those who are partnered but not married (Goldsen et al, ).…”
Section: Sgm Intimate Relationshipsmentioning
confidence: 99%
“…In addition to individual-level stressors that same-sexattracted individuals may experience, there are couple-level stressors (Frost et al 2017). Couple-level stressors include processes such as negotiating gender roles within the couple or feeling like being on display in public when interacting together in ways that would be accepted for male-female couples (e.g., holding hands; Frost et al 2017).…”
Section: Social Exchange Theory and The Minority Stress Modelmentioning
confidence: 99%